The Histone Demethylase KDM3B Promotes Osteo-/Odontogenic Differentiation, Cell Proliferation, and Migration Potential of Stem Cells from the Apical Papilla - Chen Zhang; Xiao Han; Yuncun Liang; Huina Liu; Zhipeng Fan; Jianpeng Zhang (Stem Cells International)
Understanding the regulation mechanisms of mesenchymal stem cells (MSCs) can assist in tissue regeneration. The histone demethylase (KDM) family has a crucial role in differentiation and cell proliferation of MSCs, while the function of KDM3B in MSCs is not well understood. In this study, we used the stem cells from the apical papilla (SCAPs) to test whether KDM3B could regulate the function of MSCs. By an alkaline phosphatase (ALP) activity assay, Alizarin red staining, real-time RT-PCR, and western blot analysis, we found that KDM3B enhanced the ALP activity and mineralization of SCAPs and promoted the expression of runt-related transcription factor 2 (RUNX2), osterix (OSX), dentin sialophosphoprotein (DSPP), and osteocalcin (OCN). Additionally, the CFSE, CCK-8, and flow cytometry assays revealed that KDM3B improved cell proliferation by accelerating cell cycle transition from the G1 to S phase. Scratch and transwell migration assays displayed that KDM3B promoted the migration potential of SCAPs. Mechanically, microarray results displayed that 98 genes were upregulated, including STAT1, CCND1, and FGF5, and 48 genes were downregulated after KDM3B overexpression. Besides, we found that the Toll-like receptor and JAK-STAT signaling pathway may be involved in the regulating function of KDM3B in SCAPs. In brief, we discovered that KDM3B promoted the osteo-/odontogenic differentiation, cell proliferation, and migration potential of SCAPs and provided a novel target and theoretical basis for regenerative medicine.